Effect of exogenous lignolytic enzyme-treated ragi straw on DM intake, digestibility, rumen fermentation and rumen enzymes in sheep - SRIDHAR, MANPAL; BHATTA, R; DHALI, A; SARAVANAN, M; PRADEEP, VIDYA; THAMMAIAH, VANDANA (The Indian Journal of Animal Sciences, 2015)
The present study was conducted to evaluate the effect of exogenous lignolytic enzymes harvested from immobilized Coriolus versicolor and Ganoderma lucidium on body weight, in vivo digestibility, rumen fermentation and rumen enzymes in sheep. Four groups of sheep (6-each) were fed 350 g concentrate mixture to meet the energy and protein requirement as per ICAR standards. The control sheep received ad lib. ragi straw treated with production media devoid of enzyme (G1). Test group 1 (G2) received ad lib. ragi straw treated with C. versicolor enzyme media (Enz.1) in a 1:2.5 (w/v) ratio, group 2 (G3) received ad lib. straw treated with G. lucidium enzyme media (Enz.2) in a 1:2.5 (w/v) ratio. Group 3 (G4) received ad lib. amount of straw treated with a combination of Enz.1 and Enz.2 in an equal volume in a 1:2.5 (w/v) ratio. After 40 d feeding an ADG (gd-1) of 112.5 and 107.5 was recorded in G2 and G3 as compared to 97.5 of control. A 5% increase in dry matter digestibility (DMD) of 77 .36Â±4.28 and 77.04Â±5.69% was obtained in G2 and G3. Treatment of straw with a combination of enzymes (G4) failed to show increase in either ADG or DMD. Rumen fermentation pattern did show any significant difference. The fiber degrading enzymes elicited enhancement of activity in sheep fed the supplemental enzymes. Applying lignin degrading enzymes as feed supplements for enhancing digestibility of crop residues holds promise in the immediate future.